HIDDEN CURRICULUM PENDIDIKAN ISLAM MODERAT DALAM PENGUATAN PENDIDIKAN KARAKTER: Studi Multisitus Di Madrasah - Madinatul Uyun (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Reviewing the character of today's students, many are perceived to be on an ethical threshold that is difficult to explain, even considered impossible. Many criminal and immoral acts occur, even by minors, due to the lack of character education instilled in them. The hidden curriculum of moderate Islamic education exists as an effort to provide a touch of non-radical Islamic values ​​and important unwritten material that can have a positive effect. This study aims to uncover the implementation of the hidden curriculum of moderate Islamic education in strengthening character education at Mts Muhammadiyah 09 Wotan Gresik and Mts Al-Karimi Tebuwung Gresik with the following sub-focuses: (1) implementation forms, including strategies and implementation efforts, (2) supporting factors, and (3) inhibiting factors in the implementation of the hidden curriculum. This study uses a qualitative research approach with field research and a multi-site study design. Data collection, both primary and secondary data, was conducted through observation, in-depth interviews, and documentation. Data analysis techniques included single-site analysis and cross-site analysis. The results of the study indicate that: (1) The efforts of both madrasas in implementing the hidden curriculum include environmental observations, strategy formulation, and evaluation. They also collaborate with parents or guardians to supervise students in activities of interest, habituation, and organizational activities that embody moderate Islamic education. (2) The supporting factors of both madrasas are many similarities, namely the numerous programs for religious, nationalist, and environmental awareness, student enthusiasm, teacher role models, the role and cooperation of parents, a supportive environment and community, and the large number of students residing in Islamic boarding schools and dormitories. (3) The inhibiting factors are the students' different backgrounds, resulting in differing understandings of moderate Islamic education and enthusiasm, and the lack of coordination between the Islamic boarding school and the madrasah at MTs Al-Karimi Tebuwung.